Development of STEM-Integrated Project-Based E-LKPD on Environmental Change Material - Alifah, Nila; Abidin, Zaenal (FKIP - Universitas Riau, 2025)
To equip students with 21st-century skills, appropriate and effective teaching materials integrated with technology are essential. However, an analysis revealed that while schools implemented simple project-based learning using LKPD, the existing materials only contained general questions and did not effectively facilitate project creation. This study aims to develop a STEM-integrated project-based E-LKPD on environmental change. The research follows the Research & Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. Data collection instruments included needs analysis sheets, validation sheets from material, media, and education experts, as well as teacher and student response questionnaires. The pilot study involved 36 tenth-grade students at SMAN 1 Kadugede. Validation results from experts indicated that the developed E-LKPD was highly valid for use in learning. Teacher and student response questionnaires showed very effective results, with average percentages of 94.04% and 81.02%, respectively. Student learning outcomes demonstrated an average score of 90, categorized as very good. These findings conclude that the STEM-integrated project-based E-LKPD is feasible and effective for use in STEM-based project learning.